Improved Antibacterial Properties of Fermented and Enzymatically Hydrolyzed Bee Pollen and Its Combined Effect with Antibiotics - Vaida Damulienė; Vilma Kaškonienė; Paulius Kaškonas; Rūta Mickienė; Audrius Maruška (Pharmaceuticals)
Background/Objectives: A variety of phytochemicals from different plants are collected by bees into bee pollen granules. This research focused on evaluating the effects of lactic acid fermentation and enzymatic hydrolysis on the antibacterial activity of bee pollen and its interaction with antibiotics. There is limited knowledge regarding the interactions between treated bee pollen extracts and antibiotics, and this study contributes to the field by providing new insights into the antibacterial activity of pollen subjected to eight distinct treatment methods. Methods: Bee pollen’s bacterial fermentation using a Lacticaseibacillus rhamnosus culture and spontaneous fermentation were performed. Bee pollen hydrolysis was performed using commercial enzymes, including enzyme mixtures as well as pure enzymes. The agar well diffusion assay was employed to assess the antibacterial activity against Staphylococcus aureus, Listeria monocytogenes, and Salmonella enterica serovars Enteritidis and Typhimurium, as well as their interaction with antibiotics (ceftazidime, ciprofloxacin, oxytetracycline dihydrate, and erythromycin). Results: This study showed an enhancement in bee pollen’s antibacterial activity after both fermentation and enzymatic hydrolysis. The increase varied with the pollen’s origin, treatment type, and culture used for antimicrobial tests. More than 77% of bee pollen extracts demonstrated a synergistic effect with antibiotics across all tested bacterial strains, while antagonistic interactions were comparatively rare. Conclusions: The applied treatment methods can improve the antibacterial properties of bee pollen. Bee pollen extracts, in combination with antibiotics, can enhance their effectiveness. These findings provide new insights into the potential use of bee pollen in combating bacterial infections.